2023
DOI: 10.1101/2023.06.13.544539
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The dynamics of phage predation on a microcolony

Abstract: Phage predation is an important factor for controlling the bacterial biomass. At face value, dense microbial habitats are expected to be vulnerable to phage epidemics due to the abundance of fresh hosts immediately next to any infected bacteria. Despite this, the bacterial microcolony is a common habitat for bacteria in nature. Here we experimentally quantify the fate of microcolonies ofEscherichia coliexposed to virulent phage T4. It has been proposed that the outer bacterial layers of the colony will shield … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…However, a detailed understanding of the bacterial physiology dependence of the latency time and the burst size both for single infected and superinfected cells is necessary for a more quantitative analysis of the plaque morphology. It will also help understanding dynamics of T4 attack on a growing colony [21].…”
Section: Discussionmentioning
confidence: 99%
“…However, a detailed understanding of the bacterial physiology dependence of the latency time and the burst size both for single infected and superinfected cells is necessary for a more quantitative analysis of the plaque morphology. It will also help understanding dynamics of T4 attack on a growing colony [21].…”
Section: Discussionmentioning
confidence: 99%
“…Recent work has begun to clarify the fundamentals of lytic phage propagation at high spatial and temporal resolution in the biofilm context. This research has shown that, for several species, bacteria within biofilms are often protected from lytic phage exposure (31)(32)(33)(34)(35), and that this protection is dependent on biofilm growth and architectural maturity at the time of phage introduction. When E. coli is growing in a biofilm context, for example, the hosts' interactions with lytic phages are profoundly different relative to shaken liquid culture conditions (12,31,36).…”
Section: Introductionmentioning
confidence: 99%